2019
DOI: 10.3390/foods8090407
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability of Stripped Soybean Oil during Accelerated Oxidation: Impact of Monoglyceride and Triglyceride—Structured Lipids Using DHA as sn-2 Acyl-Site Donors

Abstract: The current work aimed to clarify the effects of four structured lipids, including monoglycerides with docosahexaenoic acid (2D-MAG), diacylglycerols with caprylic acid (1,3C-DAG), triglyceride with caprylic acid at sn-1,3 and DHA at sn-2 position (1,3C-2D-TAG) and caprylic triglyceride on the oxidative stability of stripped soybean oil (SSO). The results revealed that compared to the blank group of SSO, the oxidation induction period of the sample with 2 wt% 2D-MAG and that with 1,3C-DAG were delayed by 2–3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…As Table 3 displays, a lower concentration of PUFA in sn-2 position improved the oxidative stability, which was also reported by Rocha-Uribe & Hernandez (2008). Similarly, Wang et al (2019) found that triglyceride with DHA, one of PUFAs, at sn-2 position induced the oxidation of structured lipids and promotes oxidation. It was evident in numerous studies that reducing tocopherols after CTE showed a significantly negative effect on oxidative stability.…”
Section: Correlations Between Oxidation Induction Time Dag Content Fa...supporting
confidence: 69%
See 2 more Smart Citations
“…As Table 3 displays, a lower concentration of PUFA in sn-2 position improved the oxidative stability, which was also reported by Rocha-Uribe & Hernandez (2008). Similarly, Wang et al (2019) found that triglyceride with DHA, one of PUFAs, at sn-2 position induced the oxidation of structured lipids and promotes oxidation. It was evident in numerous studies that reducing tocopherols after CTE showed a significantly negative effect on oxidative stability.…”
Section: Correlations Between Oxidation Induction Time Dag Content Fa...supporting
confidence: 69%
“…Similarly, Wang et al . (2019) found that triglyceride with DHA, one of PUFAs, at sn‐2 position induced the oxidation of structured lipids and promotes oxidation. It was evident in numerous studies that reducing tocopherols after CTE showed a significantly negative effect on oxidative stability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structured acylglycerols are a class of glycerides with speci c molecular structure or function that chemically or enzymatically change composition or position distribution of the glycerol skeleton 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Castejón and Señoráns ( 22 ) used camelina oil to enzymatically produce 2-monoacylglycerols with high α-linolenic acid content using Lipozyme TL IM, which then reacted with EPA and DHA ethyl esters aiming to produce very long-chain structured lipids as functional ingredients. Wang et al ( 23 ) first obtained 2-monoacylglycerols from algal oil and then synthesized TAGs containing caprylic acid (CA) mainly at the sn -1,3 position and DHA at the sn -2 position by reacting the monoacylglycerols with free CA in a solvent medium catalyzed by Lipozyme RM IM. In general, these multistage methods to obtain structured lipids result in higher yields of the desired TAGs, but their disadvantage is the requirement of further separation/purification steps such as evaporation and distillation, which might result in excessively high costs, considering industrial scale production processes.…”
Section: Introductionmentioning
confidence: 99%